2021
DOI: 10.3390/brainsci11080961
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Impact of Multi-Session Left Dorsolateral Prefrontal and Primary Motor Cortex Neuronavigated Repetitive Transcranial Magnetic Stimulation (nrTMS) on Chronic Pain Patients

Abstract: Repetitive transcranial stimulation (rTMS) has been shown to produce an analgesic effect and therefore has a potential for treating chronic refractory pain. However, previous studies used various stimulation parameters (including cortical targets), and the best stimulation protocol is not yet identified. The present study investigated the effects of multi-session 20 Hz (2000 pulses) and 5 Hz (1800 pulses) rTMS stimulation of left motor cortex (M1-group) and left dorsolateral prefrontal cortex (DLPFC-group), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
3
10
0
Order By: Relevance
“…Perceived disability was also significantly reduced in the a-tDCS group compared to the s-tDCS group in the present study. Although no previous studies have examined the impact of left-DLPFC a-tDCS on perceived disability in CLBP, the present findings reflect those of Freigang et al [ 67 ], who found that tDCS over DLPFC improved perceived health-related quality of life—physical functioning in those with CLBP. Taken together, these findings suggest that a-tDCS over DLPFC may modulate the cognitive and emotional appraisal of pain, which may manifest as a reduction in the pain experience for those with CLBP.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Perceived disability was also significantly reduced in the a-tDCS group compared to the s-tDCS group in the present study. Although no previous studies have examined the impact of left-DLPFC a-tDCS on perceived disability in CLBP, the present findings reflect those of Freigang et al [ 67 ], who found that tDCS over DLPFC improved perceived health-related quality of life—physical functioning in those with CLBP. Taken together, these findings suggest that a-tDCS over DLPFC may modulate the cognitive and emotional appraisal of pain, which may manifest as a reduction in the pain experience for those with CLBP.…”
Section: Discussionsupporting
confidence: 85%
“…While the mechanisms of action for tDCS and rTMS may differ, both techniques may lead to similar changes in cortical activity and, as such, have a similar effect on chronic pain [ 21 ]. Freigang et al [ 67 ] reported that, compared to motor cortex stimulation and sham, rTMS over left-DLPFC significantly reduced pain intensity in CLBP. In line with this, the present findings suggest that multi-session a-tDCS of left-DLPFC has an analgesic effect on CLBP.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has shown that the left DLPFC area is likely to be a potential target for rTMS in treating various chronic pain diseases. [13][14][15] A clinical trial suggests that rTMS in the DLPFC area can effectively relieve NPP in patients with SCI, but the total sample size was only 12. 16 A study with larger sample size is needed to verify the conclusion that rTMS in the DLPFC area is effective in treating NPP.…”
Section: Open Accessmentioning
confidence: 99%
“…Simultaneously, DLPFC area also may affect pain through several brain function networks, such as the regulation of cognitive control networks, reward/fear pathway reaction etc 12. It has shown that the left DLPFC area is likely to be a potential target for rTMS in treating various chronic pain diseases 13–15. A clinical trial suggests that rTMS in the DLPFC area can effectively relieve NPP in patients with SCI, but the total sample size was only 12 16.…”
Section: Introductionmentioning
confidence: 99%
“…Some other study groups restricted their inclusion criteria to predominantly upper limb pain patients with central post-stroke pain or complex regional pain syndrome, and they also showed that active TMS relieved pain more effectively compared with sham stimulation (Pleger et al, 2004;Picarelli et al, 2010;Ojala et al, 2021). In contrast, some studies have examined the effectiveness of rTMS in alleviating pain at different stimulation sites (Hirayama et al, 2006;Lefaucheur et al, 2006b;Jette et al, 2013;de Oliveira et al, 2014;Lindholm et al, 2015;Ayache et al, 2016;Nurmikko et al, 2016;André-Obadia et al, 2018;Galhardoni et al, 2019;Attal et al, 2021;Freigang et al, 2021;Ojala et al, 2021). We have reported that 5 Hz-rTMS to M1 relieved neuropathic pain, but that to the primary somatosensory cortex, premotor area, and supplementary motor area did not (Hirayama et al, 2006).…”
Section: Introductionmentioning
confidence: 99%